Intermediate accounting - Spiceland, J. David (McGraw-Hill/Irwin, 2007)
Adopters and reviewers praise Intermediate Accounting, 4e, by Spiceland/Sepe/Tomassini for its superior readability, strong supplements package/learning system, good EOC, real-world flavor, consistent quality; and high student engagement. SST 4e will gain support in both traditional and progressive accounting departments, especially those looking for a more concise, decision-making text that reinforces challenging concepts. At 1250 pages (200 pages shorter than the market leader), SST 4e has not sacrificed content for pages. Instead, the authors have created a flexible text with a student friendly writing style that focuses on explaining not only how to apply a procedure, but why it’s applied. SST 4e is built around a “Learning System” designed to prepare students for the new CPA exam and the business world, by emphasizing decision making. Acknowledging the diversity of students and their learning styles, the authors have created a clear text and varied supplemental materials to aid the success of every student. SST 4e also provides a flexible and consistent supplemental package for instructors.